2020
DOI: 10.1186/s12885-020-07194-5
|View full text |Cite
|
Sign up to set email alerts
|

A panel of DNA methylation signature from peripheral blood may predict colorectal cancer susceptibility

Abstract: Background: Differential DNA methylation panel derived from peripheral blood could serve as biomarkers of CRC susceptibility. However, most of the previous studies utilized post-diagnostic blood DNA which may be markers of disease rather than susceptibility. In addition, only a few studies have evaluated the predictive potential of differential DNA methylation in CRC in a prospective cohort and on a genome-wide basis. The aim of this study was to identify a potential panel of DNA methylation biomarkers in peri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
(53 reference statements)
0
13
0
Order By: Relevance
“… 12 Another research to assess the accuracy of a signature for detecting colorectal cancer patients in the training dataset and validation dataset, the results showed the AUC of 0.851 and 0.923, respectively. 13 In the present study, our diagnostic prediction signature showed better performance in differentiating cHL from normal controls and yielded new insights into the diagnosis of cHL. FOCX1 in our signature is an essential component of FOX family members which involved in carcinogenesis and the growth tumor cell and express a higher level in a variety of carcinomas.…”
Section: Discussionmentioning
confidence: 51%
“… 12 Another research to assess the accuracy of a signature for detecting colorectal cancer patients in the training dataset and validation dataset, the results showed the AUC of 0.851 and 0.923, respectively. 13 In the present study, our diagnostic prediction signature showed better performance in differentiating cHL from normal controls and yielded new insights into the diagnosis of cHL. FOCX1 in our signature is an essential component of FOX family members which involved in carcinogenesis and the growth tumor cell and express a higher level in a variety of carcinomas.…”
Section: Discussionmentioning
confidence: 51%
“…Even in the study of Heyn et al [37], in which genetic noise is removed and other sources of confounders are reduced by analyzing identical twin pairs discordant for breast cancer, they detected 403 differentially methylated sites in blood DNA between discordant twins, all with < 8% differences between the two groups. Despite the small change in magnitude, the integration of multiple epigenetic biomarkers as a predictive signature and/ or in combination with genetic markers could be of high translational value [9]. Importantly, among the CpGDMs panel detected in leukocytes, CpG sites in genes previously associated with breast cancer are described, including Cytoplasmic FMR1 interacting protein 1 (CYFIP1), reinforcing the utility of this approach in the search for biomarkers associated with breast cancer in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…A prediction model was trained on the same CpG sites (p-value < 10 –10 , N CpG = 2176) from the GSE120878 data, using a regression and decision tree algorithm 40 similar to that of Onwuka et al 41 . The prediction model was applied on the NOWAC data set of incident melanoma cases and controls.…”
Section: Methodsmentioning
confidence: 99%